(untitled) (Economic and Political Thought, 2019)
The aim of this article was to show the origin of the Transatlantic security partnership and the process that led to the creation of NATO in 1949. The article draws attention to the aggravation of East–West relations, which resulted in the outbreak of the Cold War and the transformation of the US policy after the Second World War. The worsening of the international situation also led to the initiation of Western European countries’ cooperation and integration in the area of security and defence. The outbreak of the Cold War was the result of a significant transformation of international relations consisting mainly in the emergence of two superpowers, i.e. the United States and the Soviet Union. Due to Moscow’s expansionist policy, after 1945 the United States abandoned its traditional isolationist policy in favour of active involvement in Europe’s problems. The initiatives adopted in 1947 following the new American approach, i.e. the Truman Doctrine, the Marshall Plan and the containment doctrine are analysed. Western European countries’ actions in the field of security are also taken into account, because the commitment of the United States to defend Europe was dependent on the development of cooperation in this area by the Europeans themselves. This cooperation was reflected in the Treaty of Dunkirk signed by the United Kingdom and France in 1947 and in the Treaty of Brussels signed a year later by the United Kingdom, France, Belgium, the Netherlands and Luxembourg, which led to the creation of the Western Union. The main problems that emerged during the North Atlantic Treaty negotiations and their resolution within the framework of the Transatlantic bargain, which is the basis of NATO’s functioning, are also analysed.